2020
DOI: 10.1371/journal.pone.0231950
|View full text |Cite
|
Sign up to set email alerts
|

On-Pump vs Off-Pump coronary artery bypass surgery in atrial fibrillation. Analysis from the polish national registry of cardiac surgery procedures (KROK)

Abstract: Background No single randomized study has ever before addressed the safety of On-Pump coronary artery bypass grafting (CABG) vs Off-Pump CABG in the setting of atrial fibrillation (AF) and data from small observational samples remain inconclusive. Methods and findings Procedural data from KROK (Polish National Registry of Cardiac Surgery Procedures) were retrospectively collected. Of initial 188,972 patients undergoing CABG, 7,913 presented with baseline AF (76.0% men, mean age 69.1±8.2) and underwent CABG wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 38 publications
(51 reference statements)
0
10
0
Order By: Relevance
“…Limitations of the KROK registry have been described before [7,17,21]. First and foremost, it is an observational study, and the lack of randomization means that patients in the concomitant ablation group were undoubtedly healthier than their no concomitant ablation counterparts.…”
Section: Limitationsmentioning
confidence: 99%
“…Limitations of the KROK registry have been described before [7,17,21]. First and foremost, it is an observational study, and the lack of randomization means that patients in the concomitant ablation group were undoubtedly healthier than their no concomitant ablation counterparts.…”
Section: Limitationsmentioning
confidence: 99%
“…Studies also have shown that the rate of PoAF is higher in surgical procedures performed with CPB . In another study comparing on-pump and off-pump surgeries, AF occurred more frequently after off-pump surgery [Kowalewski 2020]. Extracorporeal circulation may be a reason for this because blood electrolyte balance changes with extracorporeal circulation.…”
Section: E642mentioning
confidence: 99%
“…The risk of developing postoperative atrial fibrillation (PoAF) drops considerably after one week [Júnior 2015]. PoAF has been shown to cause low cardiac output, renal failure, prolonged ventilation support and needed intensive care unit, neurological events, and elevated mortality [Kowalewski 2020].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, attempts have been made to avoid the CPB deleterious effects and ischemia-reperfusion injury and to reduce the postoperative complications [ 4 ] questioning if off-pump coronary artery bypass grafting (OPCAB) on the beating heart may lead to diminishing the OS [ 5 ] and reduce the rate of morbidity and mortality compared with conventional on-pump CABG (i.e., CPB) [ 6 , 7 ]. However, these data are inconclusive since other studies report the opposite results [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 90%